Book Review: Robert I. Sutton & Huggy Rao, Scaling Up Excellence: Getting to More without Settling for Less, Crown Business. (March 2016) - Aggarwal, Pranati
Robert I. Sutton & Huggy Rao, Scaling Up Excellence: Getting to More without Settling for Less, Crown Business, 2014, 368 pp., 26.00. ISBN 0385347022